2004
DOI: 10.1075/wll.7.1.07san
|View full text |Cite
|
Sign up to set email alerts
|

Still errors after all those years ...

Abstract: We review some of our research findings on verb spelling errors in Dutch. The spelling of Dutch regularly inflected verb forms is governed by rules of the simple concatenative type (stem + suffix). The spelling of a subset of these verb forms is determined by morpheme-based analogy, both at the level of the stem-final letter and at the level of the inaudible (i.e., silent) suffix. This subset of verb forms causes many spelling problems, both in the learning stage and in the spelling process of experienced spel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We especially expect homophone intrusions, with the third person singular present tense being confused with the past participle, and the past tense with the adjectival past participle. Given the literature, the likelihood of a confusion is likely to be codetermined by the frequency of occurrence of the target form relative to its homophone, with fewer errors on HFverb forms than on LF-verb forms (e.g., Sandra et al, 1999Sandra et al, , 2004. We also expect that the familiarity of the verb itself instead of the specific verb form is a factor of importance.…”
Section: The Present Studymentioning
confidence: 94%
See 1 more Smart Citation
“…We especially expect homophone intrusions, with the third person singular present tense being confused with the past participle, and the past tense with the adjectival past participle. Given the literature, the likelihood of a confusion is likely to be codetermined by the frequency of occurrence of the target form relative to its homophone, with fewer errors on HFverb forms than on LF-verb forms (e.g., Sandra et al, 1999Sandra et al, , 2004. We also expect that the familiarity of the verb itself instead of the specific verb form is a factor of importance.…”
Section: The Present Studymentioning
confidence: 94%
“…We focus on Dutch verbs with two or three homophonous forms in their inflectional paradigms. Empirical evidence shows that also in Dutch many more errors are made with homophones than with nonhomophones (e.g., Assink, 1985;Sandra et al, 1999Sandra et al, , 2004. According to a rough estimate on the basis of the verbs listed in CELEX (Baayen, Piepenbrock, & Gulikers, 1995), 10% of the Dutch verbs display homophony.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indeed shown that the presence of an audible morphological marker considerably reduces verbal agreement errors in children and skilled literate adults alike. Akin to the results obtained for the French language, both Dutch children and experienced adults produce more spelling errors on regularly inflected verb forms that do not include audible differences than for those that do (Frisson and Sandra, 2002; Sandra et al, 2004). …”
Section: Introductionmentioning
confidence: 56%
“…“Silent suffix” errors with confusion of homophone verb forms are also frequent in other languages. In Dutch the 1st person verb word and the 3rd person verb wordt have the same pronunciation and are commonly confused ( Sandra et al, 2004 ). In French, there is no audible difference between the verb forms mange , manges and mangent , and ERP studies show that responses to confusion of such homophone verb forms differs from responses to confusion of heterophone verb forms like mange vs. mangez ( Carassco-Ortiz and Frenck-Mestre, 2014 ).…”
Section: Discussionmentioning
confidence: 99%